1980
DOI: 10.1136/hrt.44.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propranolol on myocardial oxygen consumption, substrate extraction, and haemodynamics in hypertrophic obstructive cardiomyopathy.

Abstract: Myocardial substrate extraction, coronary sinus flow, cardiac output, and left ventricular pressure were measured at increasing pacing rates before and after propranolol (0.2 mg/kg) in 13 patients with hypertrophic obstructive cardiomyopathy (HOCM) during diagnostic cardiac catheterisation. At the lowest pacing rate myocardial oxygen consumption varied considerably between patients and very high values were found in several individuals (range 10.1 to 57.5 ml/min). These large differences between patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…The present study demonstrates that MVO 2 in HCM patients is comparable to controls, in line with invasive investigations [21][22][23]. Similarly, previous non-invasive [ 11 C]acetate PET studies in HCM have demonstrated MVO 2 in HCM to be comparable to controls [24] or slightly decreased [2,25].…”
Section: Myocardial Oxygen Consumptionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study demonstrates that MVO 2 in HCM patients is comparable to controls, in line with invasive investigations [21][22][23]. Similarly, previous non-invasive [ 11 C]acetate PET studies in HCM have demonstrated MVO 2 in HCM to be comparable to controls [24] or slightly decreased [2,25].…”
Section: Myocardial Oxygen Consumptionsupporting
confidence: 90%
“…However, when corrected for LVM, EW and PVA generated per gram of myocardium were significantly decreased in HCM, in line with other invasive [22] and non-invasive studies [2,24]. Although not reaching statistical significant, a trend towards an increased slope of the ESPVR was observed in the HCM group, consistent with an invasive study [26].…”
Section: Myocardial Oxygen Consumptionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the verapamil dosage at the time of repeat study ranged from 240 to 480 mg/day (mean, 453), and this dosage was maintained for a mean of 6.7 days (range, 2-56) before the repeat study. The verapamil studies were performed [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] weeks (mean, 6±5) after the initial control studies.…”
Section: Study Protocolmentioning
confidence: 99%
“…mechanisms were reported for the exacerbated I/R injury of the hypertrophied hearts, including imbalance between myocardial oxygen supply and demand (1). This imbalance is caused by inadequate capillary density in relation to the increased myocardial mass and limitation of blood flow despite high oxygen demand of the myocardium (9,(33)(34)(35). Therefore, it could exacerbate the myocardial injury after ischemia (5,21,22).…”
Section: Discussionmentioning
confidence: 99%